Rethinking recycling: understanding audience perception for designing effective campaigns/ Nurul Nadiah Jamaludin, Mohd Khairulnizam Ramlie and Haslinda Md. Nazri - Jamaludin, Nurul Nadiah; Ramlie, Mohd Khairulnizam; Md. Nazri, Haslinda (Universiti Teknologi MARA, Perak, 2023)
Recycling campaigns uses various methods and platforms such as social media, advertising, mobile applications, and digital games aim to raise awareness and educate public on the importance of recycling through visual information. After almost three decades of recycling campaigns carried out by responsible party to ensure that 40 percent of waste can be reused by 2025, the community's response to the initiative is still low. Although different methods and platforms are used in recycling it still does not deliver profound impact to the public. Therefore, this study will specifically explore the audience's perception of recycling campaign which is influenced by several factors such as design elements, the uses of colour and visuals, information arrangement, as well as emotional involvement. This study is important to identify the factors that influence the audience's perception and involvement in the campaign. Through the literature review method, this study describes the elements of recycling campaign design that act as independent variables, and the audience's perception as the dependent variable. A conceptual framework is built as initiative to clearly explain the study on the factors that influence the audience's perception as reference to create an effective recycling campaign. It provides valuable guidance to campaign organizers, policy makers, and environmental advocates to plan and implement effective recycling campaign strategies for focused target group and foster positive environmental change.